2012
DOI: 10.5267/j.msl.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

A social work study on measuring the impact of age and job title on stress: A case study of hydro-power employees

Abstract: The study performs an empirical study based on the implementation of ANOVA and LSD tests to measure the impact of stress among people with different job titles and ages in a hydropower unit located in city of Esfahan, Iran. The study performed the survey among all 81 people who were working for customer service section of this company and consisted of two parts, in the first part; we gather all private information such as age, gender, education, job experience, etc. through seven important questions. In the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The other findings of this paper was that stress posed from management team had various impacts on employees with different marital status but there were no meaningful differences between married and single couples in terms of other factors posing stress such as unsuitable working conditions, fear of job stability or difficulty of job conditions. Iravani et al (2012bIravani et al ( , 2012c, in other studies, performed an empirical study based on the implementation of ANOVA and LSD tests to measure the effect of stress among people with various job titles and ages in a hydropower unit located in city of Esfahan, Iran. The study performed the survey among all 81 people who were working for customer service section of this company and consisted of two parts, in the first part; they gathered all private information such as age, gender, education, job experience, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The other findings of this paper was that stress posed from management team had various impacts on employees with different marital status but there were no meaningful differences between married and single couples in terms of other factors posing stress such as unsuitable working conditions, fear of job stability or difficulty of job conditions. Iravani et al (2012bIravani et al ( , 2012c, in other studies, performed an empirical study based on the implementation of ANOVA and LSD tests to measure the effect of stress among people with various job titles and ages in a hydropower unit located in city of Esfahan, Iran. The study performed the survey among all 81 people who were working for customer service section of this company and consisted of two parts, in the first part; they gathered all private information such as age, gender, education, job experience, etc.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that those employees who could get more experience and maintain a good educational background would more likely to stay with a firm than young employees could. Iravani et al (2012b) performed a survey to study the impact of stress among people with different job titles and ages in a hydropower unit located in city of Esfahan, Iran. They reported that there were no meaning differences among people with different job titles but people in various age groups maintained different level of stress.…”
Section: Introductionmentioning
confidence: 99%